Effigies to address violence among siblings: A psychoanalytic vision - Vallejo Castro, Ruth (Consorcio de Universidades Mexicanas A.C., 2015)
The investigation stems from reading the text Introductory Lectures on Psychoanalysis, with the idea expressed by Freud that the Oedipus complex is expanded to a family complex with the arrival of siblings, thus providing a glimpse into the fraternal complex. Therefore, the core objective of this desk research is to show how fraternal rivalry emerges, glimpsing some ways to solve it. To achieve this goal, four stories are tracked from literature: the myth of Oedipus at Colonus, the biblical accounts of Cain and Abel, Jacob and Esau, and Joseph and his brothers; these stories are analyzed with a psychoanalytic perspective, resulting in three effigies –or models– of fraternal rivalry that promote a wider understanding on the subject. The first model, named Consummated Rivalry, is the one concerning the scene where one or both contenders are killed; the second model, called Tolerated Rivalry, is that in which the siblings survive, but in uneven or unequal basis; and the third model, titled Declined Rivalry, defines that which manages to restore the brotherhood after several encounters and defiances. Each effigy deals with the conflicts arisen between siblings, as well as their solving ways, to finally establish that the second and third models are the ones that enable the transition from fraternal rivalry to brotherhood.